SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT-OBATAN PADA RSUD dr. M. SOEWANDHIE SURABAYA - Suraida, Azizah; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out and to analyze the implementation of accountancy information system of drugs inventory at RSUD dr. M. Soewandhie Surabaya.The qualitative descriptive method which is a non â hypothesis research has been applied in this research, therefore this research does not have to formulate a hypothesis. Based on the result of the research result it shows that: 1) the organization structure at RSUD dr. M. Soewandhie Surabaya overall is already well because there is separation of function or department, also the responsibility has already based on the job description, 2) the drugs inventory procedures at RSUD dr. M. Soewandhie Surabaya which consists of drugs planning, drug recording and reporting, drug storing and drug destructing have been running well because these procedures have been managed in the standard of operational procedure (SOP). 3) The drugs inventory recording system at RSUD dr. Mohammad Soewandhie Surabaya consist of drugs planning, drugs recording and drugs reporting, drugs storing, and drugs destructing have been running well because it has been supported by appropriate documents and in accordance with the drugs inventory recording system, 4) drugs reporting system at RSUD dr. M. Soewandhie Surabaya has been running well, because it has been run by using E-Inventory application and the warehouse inventory card, therefore the drugs reporting has been presented without any problems.Keywords: accountancy information system, internal control, E-Inventory.